Long-term prophylaxis in bipolar disorder. - Taylor, M; Goodwin, G (2006)
Bipolar disorder is a major cause of disability, and the prevention of relapse is a key management goal. Pharmacological interventions, effectively delivered through enhanced clinical care, are central to long-term management. This article summarises the available evidence for a range of pharmacological options, and provides guidance on common issues in clinical management in line with current practice guidelines. The use of medications for long-term prophylaxis should be considered in all patients meeting criteria for bipolar I disorder. Increasing high-quality evidence from randomised trials informs management decisions relating to both novel agents, such as lamotrigine and olanzapine, and longer-established therapies, such as lithium and valproate, in monotherapy. Medications taken long-term in bipolar disorder differ in the extent to which they protect against manic and depressive relapse. Consequently, the emerging challenge is to understand how combination treatments can enhance efficacy and effectiveness based on data from controlled trials rather than random polypharmacy. Clinical care can be enhanced with effective education about the illness, and the use of strategies to improve treatment adherence and the recognition and management of stressors or prodromal symptoms. Where available, a range of specific psychological interventions can be effective as an adjunct to medication. When discontinuation of prophylaxis is necessary, gradual tapering of dose over weeks or months is recommended.